Characteristics of the strong ground motion from the 24th August 2016 Amatrice earthquake - Marta Pischiutta; Aybige Akinci; Luca Malagnini; André Herrero (Annals of Geophysics, 2016)
The 2016 August 24 Amatrice earthquake occurred at 03:36 local time in central Apennines Italy with an epicentre at 43.36°E, 38.76°N, Istituto Nazionale di Geofisica e Vulcanologia (INGV), few kilometers north of the city of Amatrice. The earthquake ruptured a North-West (NW)–South-East (SE) oriented normal fault dipping toward the South-West (SW) (Scognamiglio et al., 2016). High values of peak ground acceleration (~0.45 g) were observed close to Amatrice (3 stations being few kilometer distances from the fault). The present study presents an overview of the main features of the seismic ground shaking during the Amatrice earthquake. We analyze the ground motion characteristics of the main shock in terms of peak ground acceleration (PGA), peak ground velocity (PGV) and spectral accelerations (SA, 5 per cent of critical damping). In order to understand the characteristics of the ground motions induced by Amatrice earthquake, we also study the source-related effects relative to the fault rupture directivity.